Design of a Semi-Automatic Charging System for Tumbler Shot Blasting Machines in the Metal Foundry Industry - Rizal Indrawan; Muhammad Taufiqurrahman; Dhika Aditya Purnomo; Fipka Bisono; Tri Andi Setiawan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The transport and distribution of flanged housing products to the fettling and shotblast tumbler zones in the metal casting industry heavily relies on manual material handling, which involves strenuous physical loads and highly repetitive motions. These conditions pose a significant risk of musculoskeletal disorders (MSDs) for operators and hinder overall production cycle efficiency. This study aims to design and develop a semi-automatic charging system as an automated material feeding solution to optimize distribution workflows and enhance ergonomic standards at the workstation. Structural analysis confirms that the entire mechanical framework, including the main chassis and lifting arms, demonstrates exceptional structural integrity and is fully secure under maximum operational loads. The actual bending stress sustained by the structure remains well below the allowable stress threshold of the specified structural steel. Furthermore, critical powertrain elements and supporting transmission components—specifically the shafts and rotary bearings—are verified to have adequate safety factors and dynamic service-life estimates for long-term production cycles. From an occupational safety perspective, implementing a panel-controlled automated system significantly improves working postures, as assessed by the Rapid Upper Limb Assessment (RULA) framework. This systemic transition completely eradicates static loads and awkward postures, thereby fostering a substantially safer, more ergonomic, and highly efficient working environment for foundry operators. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production